Bromination of Aromatic Compounds using Bromine in a Microreactor. Issue 8 (9th May 2016) - Deng, Qiulin; Shen, Ruwei; Ding, Rong; Zhang, Lixiong
Abstract: 2, 4, 5‐Trifluorobromobenzene is a valuable intermediate with important application in the synthesis of biologically active peptides and fluorescent reagents. A continuous‐flow system has been successfully developed for the synthesis of 2, 4, 5‐trifluorobromobenzene in a microreactor using FeBr3 as a catalyst, which is steadily generated in situ from the reaction of Br2 and Fe. The procedure is efficient and easy‐to‐handle, and 2, 4, 5‐trifluorobromobenzene can be obtained within minutes in high yields. Abstract : Innovative methods enabling a safer use of bromine are highly desirable. Bromination of aromatic compounds using Br2 has been successfully developed in a continuous‐flow microreactor. The catalyst FeBr3 can be steadily generated in situ from the reaction of Br2 and Fe. 2, 4, 5‐Trifluorobromobenzene is obtained within minutes in high yields by this efficient and easy‐to‐handle procedure.